Allelopathic potential of selected rice varieties - S.M. Rezaul Karim; A. M. T. A. Monowarul Momin; Mahfuza Begum (2012)
Two experiments, one in the laboratory and the other in the greenhouse, were carried out at the Bangladesh Agricultural University, Mymensingh, to evaluate the allelopathic potential of nine rice (Oryza sativa L.) varieties/lines (BR-5331-93-2-8-4, BR-5620-9-1-2, BRRI Dhan27, BR-5615-3-1-2, Lalparija, BR11, BR21, BR23 and BR25). Under laboratory condition, relay seedling technique was followed using lettuce (Lactuca sativa L.) as indicator plant. Average percent inhibition (API) in lettuce due to allelopathic effect of different rice varieties/lines was estimated. Under greenhouse conditions, double-pot technique was followed using barnyard grass (Echinochloa crusgalli L.) as indicator plant. The changes in barnyard grass plant charcters due to allelopathic effect of rice varieties/lines in comparison with the control were determined. Correlation between API values of the two experiments was studied. The API values of rice varieties/lines ranged for 22 to 40% under laboratory conditions and 30 to 35% under greenhouse condition. The ranking of rice varieties on the basis of API values under laboratory conditions was as follows: BR23 (40.51%) > BR21 (39.48%) > BR25 (39.42%) > BR11 (34.76%) > BR-5331-93-2-8-4 (34.50%) > BR-5620-9-1-2 (34.05%) > Lalparija (33.92%) > BR-5615-9-1-2 (28.87%) > BRRI dhan27 (22.76%). Under greenhouse condition, the highest API value was noticed in BR 25 (35.13%), followed by BR-5615-9-1-2 (34.50%) and the lowest API was found in BR-5331-93-2-8-4 (30.57%). The API values of rice varieties/lines under laboratory condition were positively related to the API values under greenhouse condition.